Reproduction and Characterization of Sedimentation Phenomena in Tanjung Perak Port through Numerical Simulation Using Delft3D - Camila, Adristi Nur; Murakami, Keisuke; Sajali, M. Amar; Haribowo , Riyanto (Fakultas Teknik, Universitas Brawijaya, 2025)
Tanjung Perak Port in Surabaya, one of the biggest ports in Indonesia, faces significant sedimentation problems that can affect operational capacity. This research aims to investigate these sedimentation problems using a 3-dimensional numerical model with Delft3D software, analyzing wave, tidal, and topographic changes to recommend effective sediment management. This research focuses on Tanjung Perak Harbor in Surabaya, Indonesia, using Delft3D numerical modeling to analyze sedimentation phenomena and examine topography, tidal, wave, and sediment characteristics, and river inflow data from the Mas River and Lamong Rivers. This research divides the depth into three layers with the smallest grid size dx= 10 m and dy= 10 m. Sediment diameter data, used in this simulation with an average grain size (D50) of 0.28 mm from inside the port, will be simulated simultaneously with tidal and wave motion. This simulation is for 1 month using a scale factor of 12, making the simulation equal to 1 year. From the simulation results, the effect of wave movement is relatively small. At 3 locations in the Tanjung Perak port area, sedimentation with an average change in depth of 0.8 m/year was caused by sedimentation carried from the Lamon River and Mas River. Therefore, dredging recommendations are conducted to reduce sedimentation in the port area by constructing a jetty at the mouth of the Mas River. The results showed that the average depth increase changed to 0.4 m/year after the jetty was built, but some erosion occurred around the jetty, 0.0056 m/year.